2009
DOI: 10.1177/1534734608330522
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Mechanical Noise Restores Tactile Sense in Diabetic Neuropathic Patients

Abstract: Acute application of stochastic resonance (SR), defined as a subsensory level of mechanical noise presented directly to sensory neurons, improves the vibration and tactile perception in diabetic patients with mild to moderate neuropathy. This study examined the effect of 1 hour of continuous SR stimulation on sensory nerve function. Twenty diabetic patients were studied. The effect of stimulation was measured at 2 time points, at the beginning and after 60 minutes of continual SR stimulation. This effect was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 11 publications
2
54
2
Order By: Relevance
“…However, our results revealed that stochastic resonance during these somatosensory-compromised conditions improved postural sway compared to control groups without vibratory input (Figure 8). These results are in agreement with previous research examining the effects of stochastic resonance on postural sway (Bagherzadeh Cham et al, 2016;Cloutier et al, 2009;Galica et al, 2009;Hijmans, Geertzen, Zijlstra, Hof, & Postema, 2008;Khaodhiar et al, 2003;Priplata, Niemi, Harry, Lipsitz, & Collins, 2003;Priplata et al, 2006;Stephen et al, 2012;Wang & Yang, 2012;Wei et al, 2012). We found significant improvements in sway fluctuation measurements at the vibration frequency of 220Hz.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results revealed that stochastic resonance during these somatosensory-compromised conditions improved postural sway compared to control groups without vibratory input (Figure 8). These results are in agreement with previous research examining the effects of stochastic resonance on postural sway (Bagherzadeh Cham et al, 2016;Cloutier et al, 2009;Galica et al, 2009;Hijmans, Geertzen, Zijlstra, Hof, & Postema, 2008;Khaodhiar et al, 2003;Priplata, Niemi, Harry, Lipsitz, & Collins, 2003;Priplata et al, 2006;Stephen et al, 2012;Wang & Yang, 2012;Wei et al, 2012). We found significant improvements in sway fluctuation measurements at the vibration frequency of 220Hz.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results revealed that stochastic resonance during these somatosensory-compromised conditions improved postural sway compared to control groups without vibratory input. These results are in agreement with previous research examining the effects of stochastic resonance on postural sway (Bagherzadeh Cham et al, 2016, Cloutier et al, 2009, Bagherzadeh Cham et al, 2016, Postema et al, 2009, Costa et al, 2007, Wei et al, 2012. We found significant improvements in COP measurements at vibration frequency of 220Hz.…”
Section: Resultssupporting
confidence: 93%
“…Noise-based devices, such as randomly vibrating shoe insoles [10] that apply noise during specific activities or throughout the day, may enable people to overcome functional difficulties due to age-related sensory loss [11], [64], [76], [77], [78], [79]. Furthermore, noise-based mechanical ventilators can improve gas exchange and could have a significant effect on morbidity by breaking the chain of injury propagation in acute lung injury [80].…”
Section: Clinical and Therapeutic Application Of Noisementioning
confidence: 99%